Пошук та обробка інформації - Романов, Юрій Олександрович (ТОВ "Цифра Принт", 2023)
Information searching skills are very important both for your studies and your future professional life. It is equally important to process the information obtained so that it can be shared with your audience. Studying Section 1, devoted to language varieties, you will be able to compile basic information about such phenomena as dialect, register, jargon, slang, pidgin, creole, and also national varieties of English ‒ British and American English. The focus of Section 2 is the process description, which is a very important skill four your research work and public presentation. In Section 3, five top-rated London’s attractions are presented, and you are given a chance to search for a piece of interesting information about the place you live to share it with others. Section 4 is devoted to describing a line graph: at first, its types and characteristics are considered, after which a special attention to the vocabulary and grammatical structures commonly used for a line graph description is paid. Having learned the materials proposed, you will significantly improve your information searching skills and develop the ability to process information, and consequently to logically describe the stages of the production process, select main features, and present the main trends in a summary.
Information searching and processing
Keywords: self-study guide; language varieties; national varieties of English; line graph; characteristics of a line graph